Comparison of the spiritual health and irrational beliefs of male and female undergraduate, masters and PhD students in Kashan - Sara Afshahr (Shahid Beheshti University of Medical Sciences, 2016)
For downloading the full-text of this article please click here. Background and Objectives: Irrational Beliefs leave deep impression on health, life, work, study and generally important aspects of human life. Hence the aim of this study was to compare the spiritual health and irrational beliefs of male and female undergraduate, masters and PhD students in Kashan. Materials and Methods: The present study was descriptive-comparative study. Statistical population of this study was all students studying at Kashan University in 2013-14. According to Morgan table, 364 persons were selected using available sampling method. Data collection tools were spiritual health (SWBS) and irrational beliefs (IBT) questionnaires. Data were anlyzed using SPSS software (version 22) and descriptive statistical methods, Pearson correlation coefficient and independent t-test. Results: The results showed that there is no significant difference in the score of spiritual health and irrational beliefs between the students of the Faculty of Engineering and English language (p>0.05) but there is a significant relationship between spiritual health and its dimensions with irrational beliefs, as well as between religious and existential health (p<0.01). Conclusion: It seems that irrational beliefs is affected by health, it means the students having higher health, especially mental health, will be less irrational beliefs and therefore are less susceptible to anxiety and confusion. Keywords: Mental health, spiritual health, irrational beliefs, students For downloading the full-text of this article please click here.